The molecular dynamics study of the thermal behavior of argon flow in a nanochannel with changes in nanochannel cross-section - Reza Karimi; Ali Marzban; Davood Toghraie (Results in Physics)
This article investigates argon Poiseuille flow through a copper two- and three-dimensional nanochannel via molecular dynamics simulation. In recent studies, changes in the flow cross section and the presence of solid walls in the nanochannel have been less investigated. This study investigated the influence of lateral walls in two- and three-dimensional systems, an external force, velocity field, density, temperature, flux, and thermal conductivity coefficient for a 10000-time increment using a hybrid Lennard-Jones potential function. The modeling of this research was carried out to investigate the behavior of argon flow in two- and three-dimensional nanochannels. This research is simulated in three-dimensional space using molecular dynamics methods using computer code. The results of this research show that, the increase in the number of wall atoms in a three-dimensional nanochannel causes a greater depletion of fluid kinetic energy due to the loss of temperature. The growth rate is denser in the central region of the three-dimensional nanochannel than in its two-dimensional counterpart. For square and rectangle nanochannels in the two-dimensional mode, widening the flow causes reduced density variations and minimal impact on density oscillations. In the square nanochannel, due to the small section, argon-argon and argon-copper interatomic contrasts will make the velocity of fluid atoms dominate and will make the axial velocity component more significant in the rectangle section. According to collision and diffusion mechanisms which distribute and exchange heat, there will be limited changes by altering the nanochannel section from square to rectangle. It seems that this behavior is due to similar atomic contrasts for argon-argon and argon-copper atoms. Increasing the flow section along the nanochannel transverse direction, the heat exchange caused by the interatomic collision mechanism in regions beside the wall increases, because the section increases by 20%.